Ferroelectric polymer tuned two dimensional layered MoTe2 photodetector. Issue 90 (13th September 2016) - Huang, Hai; Wang, Xudong; Wang, Peng; Wu, Guangjian; Chen, Yan; Meng, Caimin; Liao, Lei; Wang, Jianlu; Hu, Weida; Shen, Hong; Lin, Tie; Sun, Jinglan; et al.
Abstract : Ferroelectric P(VDF-TrFE) tuned the MoTe2 channel effectively with different direction of polarization. Abstract : Two dimensional material based photodetectors have attracted wide attention in recent years. In this work, a few-layer MoTe2 based phototransistor with a ferroelectric polymer P(VDF-TrFE) topgate is fabricated. The remanent polarization of the ferroelectrics could deplete the channel effectively to decrease the dark current of the device by more than one magnitude. As a result, the MoTe2 phototransistor has an appreciable photoresponse for visible light and near infrared. The device has a broad photoresponse range (0.6–1.5 μm), the responsivity and detectivity reach 16.4 mA W −1 and 1.94 × 10 8 Jones for 1060 nm light. The device works without an external gate voltage, which makes for higher reliability and lower power dissipation for practical application.